Long-term organic fertilization promotes the resilience of soil multifunctionality driven by bacterial communities. (February 2023) - Luo, Jipeng; Liao, Guangcheng; Banerjee, Samiran; Gu, Shaohua; Liang, Jiabin; Guo, Xinyu; Zhao, Heping; Liang, Yongchao; Li, Tingqiang
Abstract: Long-term intensive fertilization is a practice common around the world and gradually alters soil microbiome, however, its influences on the temporal resilience of soil multifunctionality to biodiversity loss and biodiversity-multifunctionality relationships remain poorly understood. Here, we manipulated soil biodiversity using the dilution-to-extinction approach to examine the temporal variability in individual functions, soil multifunctionality and their relationships with bacterial and fungal communities under different fertilization treatments during a 90-day re-colonization process. We found that organic fertilization accelerated the resilience of single functions and soil multifunctionality to biodiversity loss compared with mineral fertilization and unfertilized control. The fungal community was less resilient than bacterial community to disturbances caused by fertilization and dilution. Bacterial but not fungal diversity was significantly and positively related to multifunctionality, and the strength of the diversity-multifunctionality relationships in organic fertilized soil was 3- and 67-fold higher than that in unfertilized and mineral fertilized soil, respectively. Both organic and mineral nutrient inputs promoted copiotroph-dominated bacterial assemblages (including Proteobacteria and Bacteroidetes members) and suppressed oligotrophs (mostly Acidobacteria and Chloroflexi ), which paralleled multifunctionality resilience patterns in fertilized soils. β-Diversity of bacterial copiotrophs alone or in combination was significantly related to changes in multifunctionality. Random forest analysis and structural equation modeling indicated that bacterial community diversity and composition along with soil carbon and nitrogen basically determined soil multifunctionality, with 70% of the variance in multifunctionality being explained. Rare taxa from the bacterial copiotrophs were particularly important for maintaining multifunctionality. Our results underline the importance of fertilization-induced shifts in microbial ecophysiological strategies for promoting the resilience of soil multifunctionality to biodiversity loss, and the need to preserve the diversity of rare copiotrophic taxa for stable provision of ecosystem functions under future environmental change. Highlights: Organic fertiliser promoted soil multifunctionality resilience to biodiversity loss. Bacterial communities were more important than fungi for predicting multifunctionality. Multifunctionality resilience reflected fertilization-induced ecophysiological shifts. Rare copiotrophic bacteria played an over-proportional role in multifunctionality.